Examining the Efficacy of Project ECHO to Improve Clinicians' Knowledge and Preparedness to Treat Adolescent Vaping. (December 2022) - Oliver, Alexander P.; Bell, Lauren A.; Agley, Jon; Bixler, Kristina; Hulvershorn, Leslie A.; Adams, Zachary W.
As adolescent vaping reaches epidemic rates in the United States, it is imperative that pediatric clinicians have access to medical knowledge on best practices for screening, assessing, and treating vaping-related substance use. The Teen Vaping ECHO (Extension for Community Healthcare Outcomes) program was developed to offer practical learning sessions focused on clinical management of adolescent vaping. This study describes the development, implementation, and evaluation of the program's impact on participants' knowledge, attitudes, and practices regarding treatment of adolescent vaping from registration to the end of the series. Participants were generally knowledgeable about vaping at registration and reported significant increases in comfort talking with patients about vaping, counseling patients on nicotine replacement products, and frequency of implementing best-practice screening strategies at the end of the series. This study suggests ECHO programs focused on improving clinical management of adolescent vaping may increase accessibility of evidence-based care and reduce harms associated with vaping in youth.